Pacing strategy models in 1500 m male freestyle long-course swimming on the basis of the all-time ranking - Holub, M.; Prajzner, A.; Stanula, A. (International Journal of Environmental Research and Public Health, 2023)
In long-distance swimming competitions, a pacing strategy is of considerable importance for the final result and for sporting success. The paper presents the pacing strategy models of the all-time best competitors in 1500 m male freestyle long-course swimming. The top 60 scores were retrieved from official websites. The results were divided into six groups of ten swim times each, with splits of 15 × 100, 5 × 300, 3 × 500, and 2 × 750 m, and then analysis of variance was used. The main effects of the competitor group order revealed with the analysis of variance were statistically significant (p < 0.001). The group effect size turned out very high (?p2 = 0.95). Consecutive groups of competitors achieved significantly slower results. The magnitude of the interaction effects of the competitor group order and distance splits was moderate (?p2 of 0.05-0.09) and statistically not significant. The main effects of the 3 × 500, 5 × 300, and 15 × 100 m splits were high and very high (?p2 of 0.33-0.75) and statistically significant (p < 0.001). The difference between the 2 × 750 m split was statistically not significant. The achieved values of the main effects led to the following trend. In the distance split, the first and last sections did not significantly differ from each other, nor did the middle sections. However, when the middle sections and the first and last sections were compared against each other, a significant discrepancy was observed. The pacing strategies of the best athletes in the history of the competition follow a very similar parabolic trend.